Effects of vitamin C on haemolymph activity and haemocyte structure of Cherax quadricarinatus after white spot syndrome virus infection. (24th December 2021) - Zuo, Di; Liu, Xiaojie; Zhang, Yunfei; Ma, Chang'an
Abstract: In this study, we used enzymatic chemistry, histology and molecular biology to systematically study the effects of vitamin C (VC) in feed on haemocyte number and haemolymph activity in Cherax quadricarinatus . We also compared the effects of VC on the number of haemocytes, the haemocyte microstructure and the ultrastructure of C .  quadricarinatus haemocytes after White spot syndrome virus (WSSV) infection. When feed was supplemented with 800 mg/kg VC (C5 group), the number of haemocytes increased by 42.26% compared with the control group (C1 group); and the haemolymph of the C5 group had the highest agglutination activity and anti‐bacterial rate, which was significantly higher than that of the C1 group ( p  < 0.05). WSSV infection significantly reduced the total number of haemocytes, and the number of haemocytes was significantly higher in the C1 group than in the than C5 ( p  < 0.05) for up to 96 h. At 96 h, transmission electron microscopy revealed crushed perinuclear material, cell lysis, and damaged cell membranes in the C1 group, and large apparently damaged particles in the C5 group, with clear cell swelling and small particles, although the cell structure was intact. These results showed that VC enhanced the immune function of crayfish to a certain extent, maintained the integrity of the haemocyte structure and conferred an immunoprotective effect on C .  quadricarinatus against WSSV infection.